PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI UNTUK MENINGKATKAN MINAT BELAJAR SISWA IPAS KELAS V SEKOLAH DASAR - Khairunisa; Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Low interest in learning is due to the lack of media that can facilitate children's learning. Media that attracts attention and can increase students' interest in learning is needed. This research aims to develop monopoly learning media to increase the learning interest of science science students in V grade of elementary school. This type of research uses research and development using the ADDIE research model which consists of stages, namely: Analysis, Design, Development, Implementation and Evaluation. The validity test was carried out by 92% percentage material experts, 94% percentage media experts, and 90% percentage linguists. In addition to the assessment of 3 experts to find out the feasibility and practicality, it is also obtained from the assessment of teachers and students. The assessment of teacher response was 92% and the average student response was 94%. It can be concluded that monopoly learning media is declared valid and suitable for use in the learning process. The effectiveness test of monopoly media was taken from a questionnaire of student learning interests with a percentage result of 92%. Therefore, it can be stated that monopoly learning media is effectively used in the learning process.